Cyclic low dose UV-C treatments retain strawberry fruit quality more effectively than conventional pre-storage single high fluence applications - Ortiz Araque, Leidy Carolina (2018)
UV-C irradiation has been shown to reduce fruit decay and delay ripening. Based on an expected higher impact and applicability, UV irradiation treatments have been almost exclusively done before storage at relatively high doses. We evaluated the influence of the pattern of repeated short dose UV-C exposure on quality maintenance of strawberry fruit. Strawberries were subjected to the following treatments: Single-step UV: single 4 kJ m−2 irradiation prior to storage; two-step UV: two consecutive 2 kJ m−2 UV irradiations at harvest and after 4 days of storage and multi-step UV: five 0.8 kJ m−2 after 0, 2, 4, 6 and 8 days of storage respectively. A non-irradiated group was left untreated. Samples were stored at 0 °C for 13 days. All UV-C treatments decreased decay, weight loss and softening. The quality retention was higher in fruit subjected two-step and multi-step UV-C. Multiple low dose UV exposure reduced calyx browning more efficiently. Repeated low UV-C dose decreased mold and yeast counts to a higher extent. Multi-step UV treated fruit showed higher alcohol insoluble residue. Two-step UV-C treated fruit showed the highest sensorial scores. Repeated low dose UV-C treatments are more effective in preventing strawberry fruit than conventional single high-fluence pre-storage irradiation.